2010
DOI: 10.1097/hp.0b013e3181c9f7be
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Radon Absorption Efficiencies of Edible Oils Produced in India

Abstract: A study on absorption of radon by different edible oils of plant origins produced and used in India was conducted in order to identify efficient radon-absorbing oils. A comparative study of radon absorption by edible oils of India with that of olive oil, which is known as a good absorber of radon, was also carried out. The study was performed by bubbling known concentrations of radon through the oil contained in a bottle and then evaluating the bubbled oil by gamma-ray spectrometry using an HPGe detector. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Advantages of soil gas 222 Rn over the conventional sources are instantaneous natural availability, zero regeneration time required, zero cost, and excellent source stability. These features of soil gas 222 Rn are well described in the previous publications 10,14,18 . Through the semi-dynamic mode of operation, it was shown that the 222 Rn concentration could be maintained with a deviation of ± 20% from the desired value using soil gas.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Advantages of soil gas 222 Rn over the conventional sources are instantaneous natural availability, zero regeneration time required, zero cost, and excellent source stability. These features of soil gas 222 Rn are well described in the previous publications 10,14,18 . Through the semi-dynamic mode of operation, it was shown that the 222 Rn concentration could be maintained with a deviation of ± 20% from the desired value using soil gas.…”
supporting
confidence: 83%
“…In our previous publications, we demonstrated the harvesting of soil gas as a highly efficient secondary source of 222 Rn for calibration experiments 13 16 as well as a substitute for 226 Ra source in research studies 17 , 18 . Advantages of soil gas 222 Rn over the conventional sources are instantaneous natural availability, zero regeneration time required, zero cost, and excellent source stability.…”
Section: Introductionmentioning
confidence: 99%
“…The 222 Rn detection range of the scintillation cell-based monitor was 8 Bq m −3 to 50 MBq m −3 , while the ionization chamber-based monitor was 2 Bq m −3 to 20 MBq m −3 . The detailed specification of these instruments was published previously ( Al-Azmi and Karunakara, 2007 ; Karunakara and Al-Azmi, 2010 ; Karunakara et al, 2015 ; Sudeep et al, 2017 ; Sahoo et al, 2017 ; Shetty et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The detection range of ionization chamber based reference monitor is 2 Bq m -3 to 2000 kBq m -3 , while that of scintillation cell-based monitor is 8 Bq m -3 to 50,000 kBq m -3 . The details of these instruments were published earlier 1 , 14 , 16 19 . The primary calibration of the ionization chamber-based monitors was initially carried out under a Physikalisch Technische Bundesanstalt (PTB) reference atmosphere and that of scintillation cell-based monitors at BARC, Mumbai.…”
Section: Methodsmentioning
confidence: 99%
“…Soil gas was also used as a source of high 222 Rn and 220 Rn concentrations in studies aimed at developing techniques for mitigation of these gases in workplaces 16 18 . It was also used as a source of 222 Rn for studying the 222 Rn absorption capacity of edible oils 19 . But its use as a source for 222 Rn in calibration and exposure experiments in walk-in kind of chambers has not been reported earlier, and the present work is first of its kind.…”
Section: Introductionmentioning
confidence: 99%